Evaluation of feeding potential of different spider species under laboratory and greenhouse conditions (Zoo Botanica, 2025)
This study evaluates the feeding efficiency of three predatory spider species: Thyne imperialis (jumping spider), Thomisus sp. (crab spider), and Rukkidus sp. (jumping spider), under laboratory and greenhouse conditions. The spiders were tested for their potential to control guava mealybugs (Ferrisia virgate), a major pest in guava orchards. Experiments conducted in petri dishes and potted guava plants simulated natural habitats. Results revealed that Thomisus sp. exhibited the highest predatory potential, consuming an average of 6.0 ± 0.42 mealybugs within 24 hours, followed by Thyne imperialis (5.0 ± 0.40) and Rukkidus sp. (3.2 ± 0.31). The overall feeding efficiency of Thomisus sp. was 20–30% higher than the other two species across all exposure durations. Greenhouse trials confirmed similar predatory trends, demonstrating the adaptability and persistence of these spiders in semi-natural conditions. These findings emphasize the potential of Thomisus sp. and T. imperialis as effective biological control agents for managing guava mealybugs in both laboratory and greenhouse settings
Keywords: IPM; biological control; feeding efficiency; predatory spiders; natural enemies